Molding materials, moldings, and artificial marble

A specialized molding material with a balanced composition of polymer, monomer, and inorganic filler enhances the white color, transparency, and luster of artificial marble products, addressing the limitations of conventional resin compositions.

JP7625824B2Active Publication Date: 2025-02-04DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020175896
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-20
Publication Date
2025-02-04
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

Conventional resin compositions for artificial marble products, such as unsaturated polyester resin and vinyl ester resin, fail to achieve adequate white color, transparency, and luster, especially in applications requiring higher design standards.

Method used

A molding material comprising a specific combination of a polymer component, unsaturated monomer, curing agent, inorganic filler, and glass fiber, with a balanced composition of hollow filler and glass powder, is used to enhance white color, transparency, and luster in molded products.

Benefits of technology

The proposed material results in molded products with excellent white color, transparency, and luster, suitable for bathroom and kitchen fixtures, by optimizing the refractive index and particle size of the components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625824000001
    Figure 0007625824000001
  • Figure 0007625824000002
    Figure 0007625824000002
  • Figure 0007625824000003
    Figure 0007625824000003
Patent Text Reader

Abstract

To provide a molding material from which a molded article excellent in whiteness, transparency, glossiness, and image clarity is obtained, the molded article, and artificial marble.SOLUTION: Essential raw materials of a molding material are a polymer component (A) containing an unsaturated polyester (a1), an unsaturated monomer (B), a hardener (C), a thickener (D), an inorganic filler (E) containing a hollow filler (e1) and glass powder (e2), and glass fiber (F) of a fiber length of 1.5-6 mm. The inorganic filler (E) is 150-400 pts.mass to 100 pts.mass of the total amount of the polymer component (A) and the unsaturated monomer (B). The hollow filler (e1) is 0.3-10 mass% in the inorganic filler (E).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding material, a molded product, and an artificial marble. [Background technology]

[0002] 2. Description of the Related Art Conventionally, artificial marble products such as counters, wash basins, and bathtubs have been produced by molding and curing resin compositions based on thermosetting resins such as unsaturated polyester resins and vinyl ester resins.

[0003] In this context, an unsaturated polyester resin composition containing an unsaturated polyester, a copolymerizable monomer, crosslinkable polymer particles, and an inorganic filler has been proposed as a composition suitable for artificial marble having excellent transparency (for example, see Patent Document 1).

[0004] However, in applications requiring higher design quality, molded articles obtained from this composition have problems such as insufficient whiteness, transparency, image clarity, etc. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-302009 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a molding material which can give a molded article having excellent whiteness, transparency, gloss and image clarity, and a molded article and an artificial marble made from the molding material. [Means for solving the problem]

[0007] As a result of intensive research into solving the above problems, the inventors have discovered that molded articles and artificial marble excellent in whiteness, transparency, gloss, and image clarity can be obtained from molding materials containing, as essential raw materials, specific polymer components, unsaturated monomers, curing agents, thickeners, inorganic fillers, and glass fibers, and have thus completed the present invention.

[0008] That is, the present invention relates to a molding material containing, as essential raw materials, a polymer component (A) containing an unsaturated polyester (a1), an unsaturated monomer (B), a curing agent (C), a thickener (D), an inorganic filler (E) containing a hollow filler (e1) and a glass powder (e2), and glass fibers (F) having a fiber length of 1.5 to 6 mm, characterized in that the inorganic filler (E) is 150 to 400 parts by mass per 100 parts by mass of the total amount of the polymer component (A) and the unsaturated monomer (B), and the hollow filler (e1) in the inorganic filler (E) is 0.3 to 10 mass%. Effect of the Invention

[0009] The molding material of the present invention can be used to obtain molded products having excellent transparency, gloss, and image clarity, and is therefore suitable for use in bathroom components (bathtubs, waterproof pans, counters, walls), washbasin counters, kitchen counters, kitchen sinks, and other housing equipment components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The molding material of the present invention is a molding material containing, as essential raw materials, a polymer component (A) containing an unsaturated polyester (a1), an unsaturated monomer (B), a curing agent (C), a thickener (D), an inorganic filler (E) containing a hollow filler (e1) and a glass powder (e2), and glass fibers (F) having a fiber length of 1.5 to 6 mm, in which the inorganic filler (E) is contained in an amount of 150 to 400 parts by mass relative to 100 parts by mass of the total amount of the polymer component (A) and the unsaturated monomer (B), and the hollow filler (e1) in the inorganic filler (E) is contained in an amount of 0.3 to 10% by mass.

[0011] The unsaturated polyester (a1) can be obtained by reacting a polybasic acid, including an unsaturated polybasic acid, with a polyhydric alcohol.

[0012] Examples of the unsaturated polybasic acid include unsaturated dibasic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, and itaconic anhydride, and among these, maleic acid, maleic anhydride, and fumaric acid are preferred from the viewpoint of excellent strength, hot water resistance, toughness, high gloss, high image clarity, and transparency of the molded product. These unsaturated polybasic acids can be used alone or in combination of two or more kinds.

[0013] Examples of the saturated polybasic acid that can be used in combination with the unsaturated polybasic acid as the polybasic acid include phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, hexahydrophthalic acid, hexahydrophthalic anhydride, hexahydroterephthalic acid, hexahydroisophthalic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, tetrahydroterephthalic acid, tetrahydroisophthalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, and sucrose. Examples of the saturated dibasic acids include phthalic acid, 1,12-dodecanedioic acid, cyclohexanedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, and 4,4'-biphenyldicarboxylic acid, and among these, isophthalic acid, terephthalic acid, phthalic acid, and phthalic anhydride are preferred from the viewpoint of excellent strength, hot water resistance, toughness, high gloss, high image clarity, and transparency of the molded product. These saturated polybasic acids can be used alone or in combination of two or more kinds.

[0014] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, hydrogenated bisphenol A, 1,4-butanediol, an adduct of bisphenol A with propylene oxide or ethylene oxide, 1,2,3,4-tetrahydroxybutane, glycerin, trime Examples of the polyhydric alcohol include tyrolpropane, 1,3-propanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalin glycol, and 2,7-decalin glycol, and among these, propylene glycol, neopentyl glycol, and hydrogenated bisphenol A are preferred from the viewpoint of excellent strength, water resistance, hot water resistance, toughness, high gloss, and high image clarity of the molded product. These polyhydric alcohols may be used alone or in combination of two or more kinds.

[0015] The weight average molecular weight of the unsaturated polyester (a1) is 5,000 to 40,000, but is preferably 7,000 to 35,000, more preferably 8,000 to 30,000, since the glass fiber impregnation and kneading properties after the addition of a thickener are improved, a viscosity suitable for moldability is obtained, and the appearance of a molded product is improved. The weight average molecular weight in the present invention is a value calculated in terms of polystyrene based on a gel permeation chromatography (hereinafter abbreviated as "GPC") measurement.

[0016] The acid value of the solid content of the unsaturated polyester (a1) is preferably 20 to 40 mgKOH / g, because the initial thickening behavior is gentle, the glass fiber impregnation and kneading properties after the addition of a thickener are improved, and a viscosity suitable for molding is obtained, and the appearance of a molded product is improved. The acid value in the present invention is a value obtained by a measurement method in accordance with JIS K6901 (2018) 5.3.2.

[0017] The present invention contains the unsaturated polyester (a1) as the polymer component, but other polymer components such as vinyl ester (a2) can be used in combination.

[0018] The vinyl ester (a2) can be obtained by reacting an epoxy resin with (meth)acrylic acid.

[0019] Examples of the epoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol fluorene type epoxy resins, and biscresol fluorene type epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; oxazolidone modified epoxy resins; brominated epoxy resins of these resins; glycidyl ethers of phenols such as dipropylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl ethers of alkylene oxide adducts of bisphenol A, and glycidyl ethers of polyhydric alcohols such as diglycidyl ether of hydrogenated bisphenol A; Examples of the epoxy resin include alicyclic epoxy resins such as 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate and 1-epoxyethyl-3,4-epoxycyclohexane, glycidyl esters such as phthalic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, diglycidyl-p-oxybenzoic acid, and dimer acid glycidyl ester, glycidyl amines such as tetraglycidyldiaminodiphenylmethane, tetraglycidyl-m-xylenediamine, triglycidyl-p-aminophenol, and N,N-diglycidylaniline, and heterocyclic epoxy resins such as 1,3-diglycidyl-5,5-dimethylhydantoin and triglycidyl isocyanurate. Among these, bisphenol A type epoxy resins and bisphenol F type epoxy resins are preferred because they improve the balance between the fluidity of the molding material during molding and the strength, transparency, and gloss of the molded product. These epoxy resins can be used alone or in combination of two or more types.

[0020] The epoxy equivalent of the epoxy resin is preferably 220 to 470, since this further improves the toughness of the molded article.

[0021] The content of the unsaturated polyester (a1) in the polymer component (A) is preferably in the range of 50 to 100% by mass, more preferably in the range of 60 to 100% by mass, from the viewpoint of the balance between low shrinkage and transparency, gloss and image clarity.

[0022] The content of the vinyl ester (a2) in the polymer component (A) is preferably in the range of 0 to 50% by mass, more preferably in the range of 0 to 40% by mass, from the viewpoint of the balance between low shrinkage and transparency, gloss, and image clarity.

[0023] The content of the polymer component (A) in the molding material of the present invention is preferably 10 to 30% by mass from the viewpoint of the balance between low shrinkage and transparency, gloss and image clarity.

[0024] Examples of the unsaturated monomer (B) include styrene, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate alkyl ether, polypropylene glycol (meth)acrylate alkyl ether, 2-ethylhexyl methacrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isotridecyl (meth)acrylate, n-stearyl (meth)acrylate, tetrahydrofurfuryl methacrylate, isobornyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, Monofunctional (meth)acrylate compounds such as tert-butyl methacrylate, dicyclopentanyl methacrylate, hydroxyethyl (meth)acrylate, and hydroxypropyl (meth)acrylate; di(meth)acrylate compounds such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol di(meth)acrylate, and 1,4-cyclohexanedimethanol di(meth)acrylate; vinyl toluene, α-methylstyrene, diallyl phthalate, and divinyl benzene, among which styrene is preferred because the molded product has better heat resistance, water resistance, chemical resistance, and transparency. These unsaturated monomers can be used alone or in combination of two or more.

[0025] The content of the unsaturated monomer (B) in the molding material of the present invention is preferably 4 to 10% by mass from the viewpoint of the balance between low shrinkage and transparency, gloss and image clarity.

[0026] The mass ratio (A / B) of the polymer component (A) to the unsaturated monomer (B) is preferably in the range of 80 / 20 to 60 / 40, more preferably in the range of 75 / 25 to 65 / 35, from the viewpoint of a balance between low shrinkage and transparency, gloss, and image clarity.

[0027] The refractive index of the cured product of the resin composition comprising the polymer component (A) and the unsaturated monomer (B) is preferably 1.54 to 1.59, since this leads to further improved transparency of the molded product.

[0028] The curing agent (C) is not particularly limited, but is preferably an organic peroxide, such as a diacyl peroxide compound, a peroxy ester compound, a hydroperoxide compound, a ketone peroxide compound, an alkyl perester compound, a percarbonate compound, a peroxy ketal, etc., which can be appropriately selected according to the molding conditions. These curing agents (C) can be used alone or in combination of two or more kinds.

[0029] The amount of the curing agent (C) is preferably 0.3 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, based on 100 parts by mass in total of the polymer component (A) and the unsaturated monomer (B).

[0030] Examples of the thickener (D) include metal oxides and hydroxides such as magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide, and isocyanate compounds, among which magnesium oxide is preferred because it improves the balance between the handleability and moldability of the molding material, such as film peelability and finger touch. These thickeners (D) can be used alone or in combination of two or more kinds.

[0031] The thickener (D) is preferably present in an amount of 0.3 to 5 parts by mass, and more preferably 0.5 to 2.5 parts by mass, per 100 parts by mass of the total amount of the polymer component (A) and the unsaturated monomer (B), in order to further improve the in-mold fluidity of the molding material.

[0032] By using the hollow filler (e1) and the glass powder (e2) as the inorganic filler (E), a molded article having both excellent whiteness and transparency can be obtained.

[0033] Examples of the hollow filler (e1) include glass balloons, silica balloons, alumina balloons, etc., with glass balloons being preferred since they further improve the transparency of the molded article.

[0034] The average particle size (median particle size) of the hollow filler (e1) is preferably 50 μm or less, and more preferably 40 μm or less, in order to further improve the gloss and image clarity of the molded article.

[0035] The content of the hollow filler (e1) in the inorganic filler (E) is 0.3% by mass or more, preferably 0.5% by mass or more, and more preferably 0.7% by mass or more, from the viewpoint of whiteness and transparency of the molded product.

[0036] The hollow filler (e1) in the inorganic filler (E) is 10% by mass or less, preferably 8% by mass or less, and more preferably 5% by mass or less, from the viewpoints of productivity due to an increase in the viscosity of the molding material and gloss and image clarity of the molded product.

[0037] The glass powder (e2) may be glass frit, milled fiber, glass powder, or the like, with glass frit being preferred since it further improves the transparency, gloss, and image clarity of the molded article.

[0038] The average particle size of the glass powder (e2) is preferably 50 μm or less, more preferably 20 μm or less, and even more preferably 13 μm or less, in order to further improve the image clarity and gloss of the molded product.

[0039] As the inorganic filler (E), fillers (e3) other than the hollow filler (e1) and the glass powder (e2) may be used in combination, and examples thereof include aluminum hydroxide, calcium carbonate, magnesium carbonate, barium sulfate, mica, talc, kaolin, clay, silica, silica sand, gypsum, alumina, granite, silica sand, gypsum sand, titanium oxide, etc. These inorganic fillers (E) may be used alone or in combination of two or more kinds.

[0040] The refractive index of the inorganic filler (E) is preferably 1.54 to 1.59, since this further improves the transparency of the molded article.

[0041] The inorganic filler (E) is preferably 150 to 400 parts by mass, more preferably 200 to 350 parts by mass, and even more preferably 250 to 350 parts by mass, per 100 parts by mass of the total amount of the polymer component (A) and the unsaturated monomer (B), in order to further improve the appearance and smoothness of the molded product.

[0042] The glass fibers (F) have a fiber length of 1.5 to 6 mm, and more preferably 1.5 to 3 mm, since this further improves the gloss and image clarity of the molded product.

[0043] The filament diameter of the glass fiber (F) is preferably from 5 to 15 μm, since this further improves the gloss and image clarity of the molded product.

[0044] The content of the glass fibers (F) in the molding material is preferably from 1 to 17% by mass, and more preferably from 1 to 12% by mass, since this further improves the gloss and image clarity of the molded product.

[0045] The molding material may contain various additives such as a shrinkage reducing agent, a polymerization inhibitor, a colorant, an ultraviolet absorber, a viscosity reducing agent, an antioxidant, a flame retardant, a surfactant, a water repellent, and an oil repellent, as components other than the above-mentioned essential components.

[0046] The content of the low shrinkage agent such as crosslinked polystyrene in the molding material is preferably 15 mass % or less, and more preferably 10 mass % or less, of the total amount of the resin and low shrinkage agent components, since this further improves the transparency of the molded product.

[0047] The molding material of the present invention is preferably a bulk molding compound (BMC) since this improves the handling and moldability as a molding material.

[0048] The method for producing the BMC includes mixing the polymer component (A), the unsaturated monomer (B), the curing agent (C), the thickener (D), the inorganic filler (E), the glass fiber (F), and, if necessary, a low shrinkage agent, an internal mold release agent, etc., using a mixer such as a normal roll, an intermixer, a planetary mixer, a kneader, or an extruder.

[0049] The artificial marble of the present invention is obtained from the above-mentioned molding material, and the molding method is preferably the hot compression molding method of BMC, since this improves the handling and moldability of the molding material.

[0050] The heat compression molding method is, for example, a manufacturing method in which a predetermined amount of molding material such as BMC is weighed, put into a mold preheated to 100 to 180°C, the mold is clamped with a compression molding machine, the molding material is shaped, and the molding material is hardened by maintaining a molding pressure of 1 to 20 MPa, and then the molded product is taken out to obtain an artificial marble. In this case, a manufacturing method in which heat compression molding is performed in a mold having a share edge, at a mold temperature of 110 to 160°C, and at a molding pressure of 5 to 15 MPa for a specified time of 1 to 2 minutes per mm of thickness of the artificial marble is maintained.

[0051] Since the artificial marble of the present invention has excellent transparency, gloss, and image clarity, it can be suitably used for housing equipment components such as bathroom components (bathtubs, waterproof pans, counters, walls), washbasin counters, kitchen counters, kitchen sinks, etc., and building components such as walls and floors. EXAMPLES

[0052] The present invention will be described in more detail below with reference to specific examples. The acid value of the resin was measured in accordance with JIS K6901 (2018) 5.3.2, and the weight average molecular weight was measured under the following GPC measurement conditions.

[0053] [GPC measurement conditions] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.

[0054] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation Tosoh Corporation "TSKgel Standard Polystyrene A-5000"1 "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0055] (Synthesis Example 1: Synthesis of Unsaturated Polyester Resin (1)) In a 2L glass flask equipped with a nitrogen gas inlet tube, a thermometer, a reflux condenser, and a stirrer, 208 parts by mass of neopentyl glycol, 53 parts by mass of propylene glycol, 264 parts by mass of hydrogenated bisphenol A, and 290 parts by mass of isophthalic acid were charged, and heating was started under a nitrogen stream. At an internal temperature of 215°C, a dehydration condensation reaction was carried out in a conventional manner, and when the solid acid value reached 5 (mgKOH / g), the mixture was cooled to 190°C. Next, 196 parts by mass of maleic acid was added to continue the dehydration condensation reaction, and when the solid acid value reached 29 (mgKOH / g), 0.4 parts by mass of toluhydroquinone was added. The unsaturated polyester (a1-1) was dissolved in styrene monomer so that the concentration was 70% by mass, and an unsaturated polyester resin (1) was obtained. The weight average molecular weight of the unsaturated polyester (a1-1) was 10,000. The refractive index of the unsaturated polyester resin (1) was 1.55.

[0056] (Synthesis Example 2: Synthesis of vinyl ester resin (1)) In a 2L flask equipped with a nitrogen inlet tube, a thermometer, and a stirrer, 246 parts by mass of epoxy resin (DIC Corporation's "Epicron 860-C", bisphenol A type epoxy resin, epoxy equivalent 240), 750 parts by mass of epoxy resin (DIC Corporation's "Epicron 1050", bisphenol A type epoxy resin, epoxy equivalent 470), 214 parts by mass of methacrylic acid, and 0.42 parts by mass of dibutylhydroxytoluene were added, and the temperature was raised to 100°C under a gas flow in which nitrogen and air were mixed in a 1:1 ratio. 0.97 parts by mass of 2-methylimidazole was added thereto, and the temperature was raised to 110°C to carry out the reaction. When the solid acid value became 6 (mgKOH / g) or less, 0.48 parts by mass of toluhydroquinone was added, and the vinyl ester (a2-1) was dissolved in styrene monomer so that the concentration was 70% by mass, to obtain a vinyl ester resin (1). The epoxy equivalent of the epoxy resin of this vinyl ester (a2-1) was 380. The refractive index of the vinyl ester resin (1) was 1.58.

[0057] (Production Example 1: Manufacturing of handle material) A compound was obtained by kneading 100 parts by mass of a styrene solution of unsaturated polystyrene resin (styrene content 40% by mass), 250 parts by mass of aluminum hydroxide, 5 parts by mass of a white colorant, 1 part by mass of a curing agent, and 2 parts by mass of a curing accelerator. The compound obtained above was poured into a metal tray with a thickness of 15 mm, cured at room temperature for 24 hours, and then heated and cured in a dryer at 80°C for another 3 hours to obtain a cured product made of the compound. The cured product was coarsely crushed with a shear type crusher, further finely crushed with a pin mill type crusher, and then passed through 165 mesh and 28 mesh metal net sieves (JIS Z8801-1) to obtain a white granular material with a particle size of 100 to 600 μm.

[0058] (Example 1: Production and evaluation of molding material (1)) 100 parts by mass of unsaturated polyester resin (1), 0.5 parts by mass of colorant ("PT6885" manufactured by Mikuni Color Co., Ltd., white polyester toner), 1.2 parts by mass of hardener ("Perhexa HC" manufactured by NOF Corporation), 3 parts by mass of hollow filler ("3M Glass Bubbles S32-HS" manufactured by 3M Japan Ltd., glass balloon, average particle size 25 μm; hereinafter abbreviated as "hollow filler (e1-1)"), 317 parts by mass of glass powder ("CF0017-05C06" manufactured by Takara Standard Co., Ltd., glass frit, average particle size 6 to 7 μm, refractive index 1.55; hereinafter abbreviated as "glass powder (e2-1)"), 2 parts by mass of internal release agent (zinc stearate), 1.3 parts by mass of thickener (magnesium oxide), and glass fiber ("Chopped Strand" manufactured by Central Glass Fiber Co., Ltd. ECS03-670 (fiber length 3.0 mm, refractive index 1.55) (23 parts by mass) were blended and kneaded in a planetary mixer, and then aged at 40°C for 24 hours to obtain molding material (1) as BMC.

[0059] [Production of molded products (artificial marble)] Compression molding was carried out under the following conditions to obtain a molded product (1) in the form of a flat plate of artificial marble measuring 300 mm x 300 mm x 7 mm. Molding temperature: 130℃ (molded product side), 115℃ (back side) Molding pressure: 10MPa Pressurization time: 480 seconds

[0060] [Evaluation of whiteness] The whiteness (L value) of the molded article (1) obtained above was measured using "BYK spectro-guide 45 / 0 gloss" manufactured by BYK, and the whiteness was evaluated according to the following criteria. ◎: L value is 85 or more ○: L value is 80 or more and less than 85 △: L value is 75 or more and less than 80 ×: L value is less than 75

[0061] [Transparency rating] The molded article (1) obtained above was visually observed to confirm the visibility of the pattern material on the surface and in the depth direction, and the transparency was evaluated according to the following criteria. ◎: The pattern is clearly visible on the surface and inside of the molded product. ○: Pattern material is visible on the surface and inside of the molded product. △: The pattern material is slightly visible on the surface and inside of the molded product. ×: Only the pattern on the surface of the molded product is visible

[0062] [Gloss rating] For the molded article (1) obtained above, the reflectance from 0 to 2000 GU was measured at an incident angle of 20° using "BYK Gardner micro-TRI-gloss" manufactured by BYK Ltd. The value was taken as the 20° gloss value, and the gloss was evaluated according to the following criteria. ◎: 20° gloss value is 80 or more ○: 20° gloss value is 75 or more and less than 80 △: 20° gloss value is 70 or more and less than 75 ×: 20° gloss value is less than 70

[0063] [Evaluation of image clarity] The image clarity (DOI) of the molded product (1) obtained above was measured using a Rhopoint IQ-s manufactured by Konica Minolta, Inc., and the image clarity was evaluated according to the following criteria. ◎: DOI is 90 or higher ○: DOI is between 80 and 90 △: DOI is between 70 and 80 ×:DOI is less than 70

[0064] (Examples 2 to 13: Production and evaluation of molding materials (2) to (13)) Except for changing the compounding compositions to those shown in Tables 1 to 3, molding materials (2) to (13) and molded articles (2) to (13) were produced in the same manner as in Example 1, and various performances were evaluated.

[0065] (Comparative Examples 1 to 3: Production and Evaluation of Molding Materials (R1) to (R3)) Except for changing the compounding composition to that in Table 4, molding materials (R1) to (R3) and molded articles (R1) to (R3) were produced and various performances were evaluated in the same manner as in Example 1. In addition, in Comparative Example 1, BMC was not obtained due to high viscosity.

[0066] The compositions and evaluation results of the molding materials (1) to (13) obtained above are shown in Tables 1 to 3.

[0067] [Table 1]

[0068] [Table 2]

[0069] [Table 3]

[0070] Table 4 shows the compositions and evaluation results of the molding materials (R1) to (R3) obtained above.

[0071] [Table 4]

[0072] The raw materials in the table are as follows: Wetting and dispersing agent: BYK "BYK-9010" Low shrinkage agent: Aica Kogyo Co., Ltd.'s "Stafiloid GS-102R"; cross-linked polystyrene resin powder, aluminum hydroxide surface treatment product Hollow filler (e1-2): 3M Glass Bubbles S60-HS manufactured by 3M Japan Co., Ltd.; glass balloon, average particle size 24 μm Hollow filler (e1-3): 3M Glass Bubbles K46 manufactured by 3M Japan Co., Ltd.; glass balloon, average particle size 40 μm Other fillers (e3-1): "CW-308" manufactured by Sumitomo Chemical Co., Ltd.; aluminum hydroxide, average particle size 10 μm, refractive index 1.57 Other fillers (e3-2): "Softon 1200" manufactured by Bihoku Funka Kogyo Co., Ltd.; calcium carbonate, average particle size 1.8 μm, refractive index 1.63

[0073] It was confirmed that the molded articles obtained from the molding materials of Examples 1 to 13 were excellent in whiteness, transparency, gloss, and image clarity.

[0074] Comparative Example 1 is an example in which the content of the hollow filler (e1) in the inorganic filler (E) is greater than 10 mass %, which is the upper limit of the present invention, but it was confirmed that a molding material could not be produced due to high viscosity.

[0075] Comparative Example 2 is an example that does not contain the hollow filler (e1), which is an essential component of the present invention, and it was confirmed that the whiteness of the molded article was insufficient.

[0076] Comparative Example 3 is an example that does not contain the glass powder (e2), which is an essential component of the present invention, and it was confirmed that the transparency of the molded article was insufficient.

Claims

1. A molding material containing as essential raw materials a polymer component (A) containing an unsaturated polyester (a1), an unsaturated monomer (B), a curing agent (C), a thickener (D), an inorganic filler (E) containing a hollow filler (e1) and a glass powder (e2), and glass fibers (F) having a fiber length of 1.5 to 6 mm, wherein the polymer component (A) is 10 to 30 mass %, the unsaturated monomer (B) is 4 to 10 mass %, and the glass fibers (F) are 1 to 17 mass %, and the polymer component (A) and the unsaturated monomer (B) are mixed together to form a molding material. the curing agent (C) is 0.3 to 5 parts by mass, the thickener (D) is 0.3 to 5 parts by mass, the inorganic filler (E) is 150 to 400 parts by mass, the unsaturated polyester (a1) in the polymer component (A) is 50 to 100% by mass, the hollow filler (e1) in the inorganic filler (E) is 0.3 to 10% by mass, and the glass powder (e2) is 59.375 to 99.0625% by mass, relative to 100 parts by mass of a total amount of the body (B).

2. 2. The molding material according to claim 1, wherein the hollow filler (e1) has an average particle size of 50 μm or less.

3. 3. The molding material according to claim 1, wherein the thickener (D) is magnesium oxide.

4. A molded product using the molding material according to any one of claims 1 to 3.

5. An artificial marble made using the molding material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Hollow-glass-microsphere modified FRP plate and preparation method thereof

    CN104292786A

  • Unsaturated polyester resin composition

    JP1997302009A

  • Molding material and molded article

    JP2009029921A

  • Low shrink low density laminate formulation

    US20040023012A1